Complex phytohormone responses during the cold acclimation of two wheat cultivars differing in cold tolerance, winter Samanta and spring Sandra - Kosová, Klára; Prášil, Ilja Tom; Vítámvás, Pavel; Dobrev, Petre; Motyka, Václav; Floková, Kristýna; Novák, Ondřej; Turečková, Veronika; Rolčik, Jakub; Pešek, Bedřich; Trávničková, Alena; Gaudinová, Alena; et al. (Journal of plant physiology, 2012)
Hormonal changes accompanying the cold stress (4°C) response that are related to the level of frost tolerance (FT; measured as LT50) and the content of the most abundant dehydrin, WCS120, were compared in the leaves and crowns of the winter wheat (Triticum aestivum L.) cv. Samanta and the spring wheat cv. Sandra. The characteristic feature of the alarm phase (1 day) response was a rapid elevation of abscisic acid (ABA) and an increase of protective proteins (dehydrin WCS120). This response was faster and stronger in winter wheat, where it coincided with the downregulation of bioactive cytokinins and auxin as well as enhanced deactivation of gibberellins, indicating rapid suppression of growth. Next, the ethylene precursor aminocyclopropane carboxylic acid was quickly upregulated. After 3-7 days of cold exposure, plant adaptation to the low temperature was correlated with a decrease in ABA and elevation of growth-promoting hormones (cytokinins, auxin and gibberellins). The content of other stress hormones, i.e., salicylic acid and jasmonic acid, also began to increase. After prolonged cold exposure (21 days), a resistance phase occurred. The winter cultivar exhibited substantially enhanced FT, which was associated with a decline in bioactive cytokinins and auxin. The inability of the spring cultivar to further increase its FT was correlated with maintenance of a relatively higher cytokinin and auxin content, which was achieved during the acclimation period.
Keywords: listy rostlin; Triticum; Freezing; Oxidoreductases; regulátory růstu rostlin; pšenice; analýza hlavních komponent; rostlinné proteiny; oxidoreduktasy; elektroforéza v polyakrylamidovém gelu; Acclimatization; Principal Component Analysis; zmrazování; Electrophoresis, Polyacrylamide Gel; Plant Growth Regulators; roční období; Seasons; Plant Leaves; nízká teplota; Cold Temperature; aklimatizace; Plant Proteins